2011
DOI: 10.1182/blood-2010-06-289280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for response and overall survival in 282 patients with higher-risk myelodysplastic syndromes treated with azacitidine

Abstract: Prognostic factors for response and survival in higher-risk myelodysplastic syndrome patients treated with azacitidine (AZA) remain largely unknown. Two hundred eighty-two consecutive high or intermediate-2 risk myelodysplastic syndrome patients received AZA in a compassionate, patient-named program. Diagnosis was RA/RARS/RCMD in 4%, RAEB-1 in 20%, RAEB-2 in 54%, and RAEB-t (AML with 21%-30% marrow blasts) in 22%. Cytogenetic risk was good in 31%, intermediate in 17%, and poor in 47%. Patients received AZA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
291
7
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(331 citation statements)
references
References 31 publications
27
291
7
6
Order By: Relevance
“…More importantly, we demonstrate the additional value of considering MK as a separate prognostic category, and our observations in this regard are consistent with the adverse prognostic impact of MK in other myeloid malignancies including acute myeloid leukemia and primary myelofibrosis [9,14]. Others have suggested that prognosis was related more with the complexity of karyotype rather than MK [15] and the possibility remains that these observations might be influenced by specific therapy [16].…”
Section: Resultssupporting
confidence: 88%
“…More importantly, we demonstrate the additional value of considering MK as a separate prognostic category, and our observations in this regard are consistent with the adverse prognostic impact of MK in other myeloid malignancies including acute myeloid leukemia and primary myelofibrosis [9,14]. Others have suggested that prognosis was related more with the complexity of karyotype rather than MK [15] and the possibility remains that these observations might be influenced by specific therapy [16].…”
Section: Resultssupporting
confidence: 88%
“…In total 7 patients with MDS or CMML and 2 patients with AML receiving CC‐486 monotherapy in this study attained CR or PR, including, importantly, patients for whom previous DNMTi therapy had failed. While multiple studies have shown injectable azacitidine can improve OS in higher‐risk MDS and AML without requiring CR5, 7, 8, 9, 37; the effect of CC‐486 on OS has not yet been reported and was not captured in this phase 1 study, but is under investigation in an ongoing phase 3 trial of CC‐486 in patients with MDS (NCT01566695).…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral azacitidine has been extensively evaluated in patients with MDS, chronic myelomonocytic leukemia (CMML), and AML in large randomized clinical trials,5, 6, 7 in regional registry studies,8, 9, 10, 11, 12, 13 and in numerous smaller retrospective analyses of patients treated in community practice 14, 15. These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21.…”
Section: Introductionmentioning
confidence: 99%
“…Several predictors of the response to demethylating agents have been proposed, including MDS duration before therapy, prior therapy or previous low doses of aracytine, BM blasts 415%, abnormal karyotype, p15 INK4B gene promoter methylation or hypermethylation of a set of 10 different genes. 13,14 However, changes in CDKN2B, CDH1, DAPK1 and SOCS-1 gene expression upon therapy did not correlate with the response. 15 Our results show that Fas re-expression correlated with the response and that low Fas protein expression at diagnosis, which associated with hypermethylation of the FAS gene promoter, is a predictive biomarker of the response to azacitidine, independently of IPSS and prior therapy, even if the re-activation of Fas may not be the sole determinant of the response.…”
Section: Letters To the Editormentioning
confidence: 94%